Analysis of Antimicrobial Compound in Ziziphus Mauritiana Extract using Attenuated Total Reflection-Fourier Transform Infrared (ATR-FTIR) - Khairina Idris; Nurhanini Nahlul Muna Yusof; Tg Ainul Farha Tg Abdul Rahman; Liyana Amalina Adnan; Nurdalila A’wani Abdul Aziz (USIM Press, 2024)
MJoSHT2020, Volume 7, Special Issue, eISSN: 2601-0003